Women of Assur and Kanesh: texts from the archives of Assyrian Merchants - Michel, Cécile (Writings from the Ancient World Ser., 2020)
Cover -- Contents -- Series Editor's Foreword -- Acknowledgements -- Abbreviations and Conventions -- List of Figures -- Map of the Old Assyrian Period -- Introduction -- Chronology, Calendars, and Metrology -- Marriage and Divorce -- Women and Family -- Housewives -- Businesswomen -- Religion and Social Mores -- Portraits of Assyrian and Anatolian Women -- Texts Edited -- Bibliography -- Indexes.